HUBUNGAN DISRITMIA THALAMOKORTIKAL PADA GAMBARAN EEG KUANTITIATIF DENGAN KRONISITAS NYERI KEPALA PRIMER - , KARL OTTO PANGGALO, dr Ahmad Asmedi, M.Kes.,SpS(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chronic daily headache (CDH) is one of the health issue that frequently occurred and affected 3% - 5% of world population. One of the possible cause of chronity on CDH is thalamocortical dysritmia (TCD). This study used observation cross sectional design. Main factors that analayzed was increasing of theta spectral power to alpha spectral power on CDH patients according to Quantitative EEG (QEEG) examination and increasing of absolute spectral power generally on CDH group compared to control group. Eighty subjects (80) included, 40 subjects on CDH group and subject group respectively. Mean rank theta spectreal power found to be higher compared to mean rank alpha spectral power (46.80 vs 34.20), statistically significant (p = 0.015). Mean rank theta spectral power higher on CDH group compared to control group (45.38 vs 35.62), not significant statistically ( p = 0.06). Occurrence of theta spectral power dominance to alpha spectral power on CDH group was 26 over 40 subjects